Culture on Two Wheels : The Bicycle in Literature and Film - Shea, Daniel P.; Withers, Jeremy (Book collections on Project MUSE., 2016)
"Analyzes how print and visual texts of various kinds reflect, refract, and respond to the social and political significance of the bicycle from its origins in the nineteenth century to the present"--